Enveredando pela poesia de resistência de Agostinho Neto : a palavra enquanto arma - Ramos, Celiomar Porfirio (2016)
This dissertation is a study about the masterpiece Sagrada Esperança (1985), by the Angolan poet Agostinho Neto. The aim of this writing is to discuss how the poet takes his poetry as a weapon in favor of Angola’s liberty and, in the meantime, as an instrument of raising Angolan people’s awareness. This work is organized under the hypothesis that his poetry is taken as a weapon with the aim to motivate Angolan population to fight against the colonial process in order to claim the construction a national identity. Besides that, it aims to report the atrocity by the colonialist, as well as to spread the hope for better days. Throughout this dissertation, we have found that the hypothesis raised in the beginning has been confirmed throughout the research. That was possible to be observed especially due to interpretative analysis of selected poems: “Velho negro”, “Saudação” and “As terras sentidas”, which indicates, as well as other poems from the same masterpiece, the author’s literary involvement with and the commitment to the national liberty to the point of making his poetry a weapon of fight. The research area in which this work is contextualized is literature and social life and hence taking the literary text to reflect on society. In order to theoretically support this work, the critical literary text by Antonio Candido, titled Literatura e Sociedade (2006), and by other theorists and reviewers who follow this same area are provided as basis.